Construire des ressources relationnelles pour franchir des frontières multiples : Trajectoires de jeunes Tunisiens - Hasnia-Sonia Missaoui (L’Année du Maghreb)
This article presents the results of a survey conducted between 2014 and 2016 among young adults from the Tunisian-Algerian border region of Kef. We collected several social trajectories of “unemployed graduates” a few years after the overthrow of President Zine el-Abidine Ben Ali’s regime on January 14, 2011 in order to understand how the bubbling of democratic expression carried by powerful collective mobilization movements linked to the end of the dictatorship can influence the daily life of an age group that is particularly mediatized but invisibilized or instrumentalized by the public authorities. These trajectories show us first of all the disenchantment of an age group with blurred contours that is linked to the situations of socio-economic injustice that they experience on a daily basis. These young people express a feeling of exclusion in the face of the many inequalities suffered in the family circle, confronted with numerous inter-generational conflicts as well as the weak presence of the public authorities. These demands, which are hardly heard by the authorities and the elites, express a demand for more social equality in everyday life, more freedom of movement and, more generally, recognition by the State. The injustices that young 'unemployed graduates' experienced daily are also forms of social demand. In other words, we can see a real process of identity building among citizens in training and the emergence of a “social critique” aimed at combating social immobilism and “post-revolutionary” disenchantment. In this difficult context, social and geographical mobility are therefore necessary resources for young adults in order to take the initiatives they feel are necessary to compensate for the shortcomings they experience because of their social and geographical origin. Young “unemployed graduates” suffer from many forms of precariousness, which they accumulate, as well as from social and territorial inequalities. However, they develop many professional projects. These generally aim to access micro-entrepreneurship and/or a migratory project, whether these mobilities are realised or planned, and whether they are short or long distance. They thus show a strong determination to fight the social immobility to which they feel assigned and, to do so, they multiply the crossing of social and territorial universes. Their initiatives are sometimes not very visible to those around them. They start by building what they lack most, i.e. relational skills in order to create circles of solidarity, friendship, mutual aid and professional advice, in Tunisia and sometimes also abroad. They then combine these skills with different forms of mobility in order to build their own trajectory and try to escape the identity assignment of citizens on the margins of society. In order to grasp the different key moments and places that participate in the elaboration of their future, we have mobilised the usual tools of comprehensive sociology (interviews, life stories, observations) by conducting interviews in Tunis and in the Kef region. This information was then analysed using methods relating to the analysis of social relations, in particular the so-called “name generator” protocol. By proceeding in this way, it becomes possible to highlight individual trajectories that are similar to chance encounters, often random, but which the people concerned know how to grasp. However ephemeral they may be, these contacts are in fact likely to provide essential resources for access to social autonomy for those who build them. These links, which may be one-off or last a lifetime, can counterbalance “vertical” aspirations that are often disappointed and the constant feeling of being up against the wall. They can sometimes be a real resource for upward mobility, but more generally, as collective commitment wanes a few years after the fall of the dictatorship, they restore a sense of belonging and can be an antidote to disenchantment.